Isoquinolinium-based photosensitizers with aggregation-induced emission characteristics for highly efficient photodynamic combat of viruses. (7th September 2022) - Gu, Meijia; Wu, Ming-Yu; Yuan, Yuncong; Ho, Po-Yu; Zhou, Zhou; Zhao, Engui; Shen, Chao; Chen, Sijie
Abstract : This work presents the highly efficient photodynamic combat of viruses by employing three isoquinolinium-based photosensitizers with aggregation-induced emission characteristics. Abstract : Because of the prevalence of COVID-19, people are becoming increasingly aware of the importance of disinfection, which necessitates the development of convenient and efficient methods for inactivating pathogens. In this work, we report the application of three isoquinolinium-based aggregation-induced-emission-active photosensitizers (PSs) for photodynamic inactivation (PDI) of viruses at a low light intensity of 9 mW cm −2 . These three PSs could highly efficiently sensitize the production of reactive oxygen species and are applied to PDI of viruses. Their inactivation effects on viruses are evaluated by checking the cytopathic effect through examining the morphology of their host cells, investigating their protein expression in host cells by Western blot, immunofluorescence imaging of the viral proteins in host cells, quantifying the viral RNA levels after infection, and viral titering-median tissue culture infectious dose (TCID50 ) assay. The experimental results obtained clearly demonstrate the excellent PDI effect of these three PSs on viruses. Besides, we also explore the feasibility of employing these PSs for PDI of viruses on simulated high-touch surfaces, such as stainless steel and glass slides, on which these PSs demonstrate an even better PDI effect on all the three tested viruses. The PDI method described in this work is expected to innovate the disinfection practice in public areas.